ANALISIS PENGARUH SOSIALISASI PERPAJAKAN, PEMERIKSAAN PAJAK, DAN PENAGIHAN PAJAK TERHADAP PENERIMAAN PAJAK PENGHASILAN WAJIB PAJAK BADAN PADA KPP PRATAMA MEDAN BARAT - Aritonang, Monica Deskezia; Saragih, Joana L. (LPPM Universitas Katolik Santo Thomas Medan, 2024)
The purpose of this study was to determine the effect of tax socialization, tax audit, and tax collection on corporate taxpayer income tax revenue at KPP Pratama Medan Barat. The number of corporate taxpayers sampled in this study were 100 respondents. The sampling method used in this study uses the slovin technique, while the data collection method used in the data processing used is multiple linear regression analysis. The results of this study indicate that tax socialization, tax audits, and tax collection are proven to have a positive effect on income tax revenue. The variable that has the most significant influence on income tax revenue is tax audit with the largest beta value among other independent variables